2021
DOI: 10.2478/raon-2021-0030
|View full text |Cite
|
Sign up to set email alerts
|

Microwave ablation compared with radiofrequency ablation for the treatment of liver cancer: a systematic review and meta-analysis

Abstract: Background Guidelines have reported that although microwave ablation (MWA) has potential advantages over radiofrequency ablation (RFA), superiority in efficacy and safety remain unclear. Aim of the study is to compare MWA with RFA in the treatment of liver cancer. Methods Meta-analysis was conducted according to the PRISMA guidelines for studies published from 2010 onwards. A random-effects model was used for the meta-analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 42 publications
(172 reference statements)
2
19
1
2
Order By: Relevance
“…RFA, as one of the major approaches for clinical non-surgical treatment of liver cancer, has the advantages of less trauma and fewer complications [ 20 ]. However, a number of studies have shown that liver cancer patients had a higher incidence of recurrence after RFA [ 21 , 22 ], so it is of great significance to predict the curative effect and prognosis of patients after RFA early.…”
Section: Discussionmentioning
confidence: 99%
“…RFA, as one of the major approaches for clinical non-surgical treatment of liver cancer, has the advantages of less trauma and fewer complications [ 20 ]. However, a number of studies have shown that liver cancer patients had a higher incidence of recurrence after RFA [ 21 , 22 ], so it is of great significance to predict the curative effect and prognosis of patients after RFA early.…”
Section: Discussionmentioning
confidence: 99%
“…HCC patients after RFA treatment show low recurrence and mortality rate, which achieves similar curative effect as surgery to some extent ( 33 36 ). Previous studies also supported low recurrence rate and only mild adverse reactions, including fever, neutrophils, local pain and minor thermal damage in peripheral organs ( 37 39 ).…”
Section: The Principle Of the Ablation Techniquesmentioning
confidence: 59%
“…Although it is currently the preferred treatment for FNH, some scholars ( Virgilio and Cavallini, 2018 ) believe that surgical resection-related complications and mortality are serious and unacceptable for the treatment of benign diseases. The common complications of thermal ablation for liver cancer mainly include subcapsular hematoma, abdominal skin burn and pleural effusion ( Spiliotis et al, 2021 ). These complications may also occur during FNH treatment.…”
Section: Discussionmentioning
confidence: 99%